Halvautomatisk ekserpering av anglisismer i norsk - Andersen, Gisle (Nordiske Studier i Leksikografi, 2010)
This paper reports on the status of ongoing corpus-based lexicographical work within the framework of the Norwegian Newspaper Corpus project (http://avis.uib.no/). Specifically it describes the work flow, tools and methods used in the identification and analysis of new anglicisms in Norwegian. The identification of recent English loan words serves a variety of purposes, including term extraction and the development of lexicography and terminology, and language political purposes such as surveying the amount and inventory of English loan words in various usage domains. While previous work in Norwegian lexicography has generally relied on manual methods for excerpting new words – and for identifying anglicisms among the new words, the current project is an effort to develop tools which automatises the process of identifying, segmenting and analysing new loan words from English. The article describes the overall workflow and focuses especially on alternative methods for identifying anglicisms (lexicon-based, n-gram-based, combinatory methods), as well as the relevance of these methods for lexicography.